Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera: Ensifera: Stenopelmatoidea) XXIV: Update on the Raspy Cricket species’ checklist with some comments - Bian, Xun (Zootaxa, 2023)
This paper lists the updated Chinese Gryllacrididae checklist, including 24 genera and 174 species/subspecies. One new replacement name and the type information of Neolarnaca longipenna Bian & Shi, 2016 are provided. Lastly, one intraspecific variation of Larnaca (Larnaca) nigrifrons is briefly described and illustrated.